Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Dari Sudut Pandang Pasien Dan Pendamping Pasien (Studi Kasus Di RS Medistra, Jakarta) - Wardani, Beny Mutiara; Efendi, Efendi (Jurnal Manajemen, 2014)
Along with the increasingly competitive business environment and changes in the living standards, people have changed their mindset in choosing and making judgment of hospital services. The change of paradigm requires hospitals to maintain quality of services to service users in order to achieve organizations goals. Therefore a study is conducted to determine the effect of the hospital service quality on satisfaction from the perspective of patient and their attendants. In collecting the data, the authors distribute the questionnaires in RS Medistra Jakarta on February 4 to March 5, 2013. Questionnaire was distributed to 123 patients and 123 attendants by using non-probability sampling, which is judgmental sampling. Data were analyzed using SPSS version 17 by Regression testing method.The results showed that simultaneously and partially there is an influence of Infrastructure, Quality Personnel, Process of clinical care, Administrative procedures, safety indicator, Image Hospital, Social responsibility, trustworthiness of the hospital on Customer Satisfaction from the perspectives of patient and their attendants.        Key words: service quality, customer satisfaction, hospital, Jakarta